2010
DOI: 10.1002/hed.21494
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive variants of papillary thyroid carcinoma

Abstract: A number of histologic variants of well-differentiated papillary carcinoma have been found to be associated with more aggressive tumor behavior. Tall cell, columnar cell, diffuse sclerosing, solid/trabecular, and insular variants of well-differentiated papillary thyroid cancer are all potentially more aggressive than conventional papillary thyroid cancer. When subjected to multivariate analysis, however, evidence that the histologic subtype of tumor is an independent predictor of outcome is weak. Rather, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
107
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 37 publications
4
107
0
8
Order By: Relevance
“…Some authors have suggested that this difference should be attributed to higher rates of aggressive pathologic features rather than variant histology, and they do not recommend aggressive treatment based on histology alone (27,37,38). Contrary studies that control for these aggressive features show that histology remains an independent risk factor for adverse outcomes, and many advocate total thyroidectomy with prophylactic central lymphadenectomy in aggressive variants regardless of tumor size (8,16,28,30,39). None of these studies has examined mDSV and mTCV specifically, and it is unclear whether histology alone warrants more extensive surgery in tumors £ 1 cm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested that this difference should be attributed to higher rates of aggressive pathologic features rather than variant histology, and they do not recommend aggressive treatment based on histology alone (27,37,38). Contrary studies that control for these aggressive features show that histology remains an independent risk factor for adverse outcomes, and many advocate total thyroidectomy with prophylactic central lymphadenectomy in aggressive variants regardless of tumor size (8,16,28,30,39). None of these studies has examined mDSV and mTCV specifically, and it is unclear whether histology alone warrants more extensive surgery in tumors £ 1 cm.…”
mentioning
confidence: 99%
“…Performing a redo prophylactic ipsilateral central lymphadenectomy at the time of completion thyroidectomy is not common practice, even though it has been shown to be safe if performed in a highvolume center with experienced surgeons (40). Preoperative diagnosis of DSV and TCV is difficult (8,39). TCV and DSV have unique cytopathologic characteristics, and although diagnostic criteria have not been rigorously evaluated, several reports indicate that finding tadpole-shaped cells or inflammation and squamous metaplasia on FNA can raise preoperative suspicion of TCV or DSV (19,20,22,41,42).…”
mentioning
confidence: 99%
“…Grant et al, have divided 963 patients with thyroid surgery with local recurrence in the thyroid bed and recurrence in the thyroid remnant. They found that mortality rates were higher for patients with recurrence in the thyroid bed [26]. Disease-free survival rates for these cases appeared to be lower than patients with recurrent disease at the thyroid remnant [1,2].…”
Section: Citationmentioning
confidence: 98%
“…2,3) Established unfavorable prognostic factors of PTC are age at diagnosis, tumor size, extrathyroidal extension, lymph node metastasis, histologic subtype (tall cell, columnar cell, diffuse sclerosing, and insular variants), incomplete surgery, and omitted or insufficient radioactive iodine therapy. 4,5) In recent years, there has been wider acceptance about the critical role systemic inflammation plays in the evolution of cancer. [6][7][8] In the physiologic inflammatory process, wound healing is self-limited by balancing anti-and pro-inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%